Is cash still king? Exploring how township retailers navigate physical and digital money - Modise, Tshwanelo (Graduate School of Business (GSB), 2025)
Despite the rise of digital payments, cash remains integral to township economic tapestry, valued for its relational and adaptable qualities that digital alternatives have yet to fully emulate. This study challenges the conventional 'cash versus digital payments' dichotomy by presenting township retailers as informal financial intermediaries who navigate the sophistication of digital payments alongside the deeply ingrained social and economic functions of cash. Guided by Orlikowski's (1992) Structurational Model of Technology, this research reveals how socio technical dynamics shape payment behaviours. It asserts that although digital payments are promoted as tools of financial inclusion, cash reflects social interactions and relational norms that digital methods have yet to fully replicate. Township businesses creatively navigate this dual payments system with situational adaptability, demonstrated through unique practices like ‘sweets-for-change,' which restructure the role of cash in the township business landscape. Through an evaluative lens, this research examines whether digital payments fulfil their promise of financial inclusion in cash-based economies, and advocates for financial solutions that recognise and leverage the symbiotic relationship between cash and digital payments. This research concludes that while cash may not undisputedly be king, it remains a vital component of the economic fabric in townships, coexisting with digital payments in a way that reflects the adaptability and resilience of these communities.